Analisa Peluang dan Ancaman Perdagangan Bebas Produk Pertanian (Studi Kasus Pada Perdagangan Kelapa Sawit antara Indonesia dengan Thailand) - Muhammad Mirwansyah Ramadhan; Daspar (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Free trade in agricultural products, especially crude palm oil (CPO), has a significant impact on the global economy, including for producing countries such as Indonesia and Thailand. Indonesia, as the world's leading CPO producer, faces the challenge of increasing Thailand's production capacity, which is also growing in this sector. This study aims to analyze the opportunities and threats in CPO trade between Indonesia and Thailand, focusing on the influence of free trade policies in the ASEAN region. The results of the study show that although Indonesia has a comparative advantage in CPO production, challenges such as tight price competition, dependence on crude CPO exports, and pressure on environmental desires can affect Indonesia's competitiveness in the international market. On the other hand, great opportunities arise through downstream policies, strengthening logistics infrastructure, and regional cooperation that can strengthen Indonesia's position. This study recommends policies to increase the added value of palm oil products, improve distribution infrastructure, and improve poverty standards so that Indonesia can maintain its position as a global market leader in the palm oil industry.